Efficacy of fungicides alone and in combination with insecticides on foliar diseases of onion (Allium cepa) in rabi season - and R.P. GUPTA, R.C. GUPTA* (Indian Phytopathology, 2014)
trial was conducted on onion variety Agrifound Light Red to test the combined efficacy of fungicides and insecticides on foliar diseases of onion during rabi, 2010-11, 2011-12 and 2012-13 at Research Farm, Chitegaonphata, National Horticultural Research and Development Foundation (NHRDF), Nashik. The fungicides namely mancozeb @ 0.25%, propiconazole @ 0.1%, copper oxychloride @ 0.25%, tricyclazole @ 0.1% and hexaconazole @ 0.1% were tested alone and in combination with insecticides namely methomyl @ 0.8g/L, carbosulfan @ 2ml/L and profenofos @ 1ml/L in the present study. The pooled data of three years revealed that, maximum percent disease control of stemphylium blight (59.81%) as well as highest gross yield (326.60q/ha) and marketable yield (317.44q/ha) of onion was recorded with combined spray of mancozeb @ 0.25% + methomyl @ 0.8g/L at 30 DAT, propiconazole @ 0.1% + carbosulfan @ 2ml/L at 45 DAT and copper oxychloride @ 0.25% + profenofos @ 1ml/L at 60 day after transplanting (DAT). The maximum increase in marketable yield (31.64%) of onion bulbs was also recorded in the same treatment over untreated check. The highest incidence (36.67%) of stemphylium blight and lowest gross (248.10q/ha) as well as marketable yield (239.89q/ha) of onion were recorded in untreated check. Purple blotch and Colletotrichum blight did not appear during the entire cropping season in onion crop. The study revealed that combined sprays of fungicides and insecticides effectively managed the stemphylium blight disease as well as increased yield of onion bulbs during rabi season under Nashik area of Maharashtra.